Lhermitte-Duclos-Cowden Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Two unrelated patients with clinical characteristics of both Lhermitte-Duclos disease and the autosomal dominant Cowden disease are reported from the Department of Neurology, University Hospital, Leiden, The Netherlands.